Strong and machinable carbon aerogel monoliths with low thermal conductivity prepared via ambient pressure drying. (November 2016) - Jia, Xianfeng; Dai, Bowen; Zhu, Zhaoxian; Wang, Jitong; Qiao, Wenming; Long, Donghui; Ling, Licheng
Abstract: Carbon aerogels are among the most attractive porous carbon materials currently, but their real-world applications are greatly limited by their high cost, complicated preparation process and low mechanical properties. Herein, we report a very facile route to prepare lightweight but mechanically strong carbon aerogel monoliths (CAMs), through a sol-gel polymerization of linear phenolic resin and hexamethylenetetramine (HMTA), followed by ambient pressure drying and carbonization. The good capability of linear phenolic resin with ethanol could induce the formation of large polymer particle and good particle connectivity, affording robust network to suppress the collapse during the ambient drying. The synthesis is scalable and flexible, permitting a facile tailor of density, porous structure and mechanical strength by adjusting the ratio of phenolic resin to HMTA and phenolic resin concentration. The obtained CAMs possess macroporous/microporous hierarchical structure with low density as low as 0.07 g cm −3, high mechanical strength of 0.9–5.0 MPa and low thermal conductivity (0.032–0.069 W m −l  K −1 ). Further CO2 activation can greatly develop the microporosity without sacrificing the monolithic structure. Moreover, as-prepared CAMs can be fabricated in large sizes, as well as being post-machined into many shapes and sizes for potential applications.